Key Role of the Influenza A Virus PA Gene Segment in the Emergence of Pandemic Viruses - Lutz, Michael M. (Viruses, 2020)
Influenza A viruses (IAVs) are a significant human pathogen that cause seasonal epidemics and occasional pandemics. Avian waterfowl are the natural reservoir of IAVs, but a wide range of species can serve as hosts. Most IAV strains are adapted to one host species and avian strains of IAV replicate poorly in most mammalian hosts. Importantly, IAV polymerases from avian strains function poorly in mammalian cells but host adaptive mutations can restore activity. The 2009 pandemic H1N1 (H1N1pdm09) virus acquired multiple mutations in the PA gene that activated polymerase activity in mammalian cells, even in the absence of previously identified host adaptive mutations in other polymerase genes. These mutations in PA localize within different regions of the protein suggesting multiple mechanisms exist to activate polymerase activity. Additionally, an immunomodulatory protein, PA-X, is expressed from the PA gene segment. PA-X expression is conserved amongst many IAV strains but activity varies between viruses specific for different hosts, suggesting that PA-X also plays a role in host adaptation. Here, we review the role of PA in the emergence of currently circulating H1N1pdm09 viruses and the most recent studies of host adaptive mutations in the PA gene that modulate polymerase activity and PA-X function.